Enhancing the role of reporting in attaining the Sustainable Development Goals : integration of environmental, social and governance information into company reporting (UN New YorkUS, 2016)
Elaborates on criteria and principles for the selection of core indicators for the goals for company reporting and proposes specific indicators covering economic, environmental, social and institutional information based on the global monitoring indicators for the goals, existing initiatives on sustainability reporting and prevailing practices.
Keywords: REPORTING SYSTEMS